Assistive Technology in Mathematics Learning for Visually Impaired Students - Daroni, Gangsar Ali; Gunarhadi, Gunarhadi; Legowo, Edy (Universitas Islam Negeri Raden Intan Lampung, 2018)
Mathematics is an important subject to be learned by all children. Visually impaired children experience obstacles in following the process of mathematics learning caused by abnormalities. Visually impaired students experience obstacles in the process of thinking at the disequilibrium stage and low understanding of concepts when studying mathematics. It caused them to experience difficulties when doing math problems. Assistive technology is a technology created specifically to improve or maintain the functional ability of children with special needs in order to accomplish tasks that hard for them to do. Assistive technology for visually impaired children is made by maximizing the abilities that the children still possess and helping them to get a clearer mathematical concept. This article is a literary study which aims to provide information about the difficulty for the visually impaired students in mathematics learning and assistive technologies that have been developed to support the learning. This article can be used as the basis for developing new assistive technology in mathematics learning. Assistive technology is needed to help children with visual impairment in following the learning of mathematics and to optimize the ability of the children in learning mathematics.